IMPROVING DISSEMINATION OF WEATHER INFORMATION SERVICES THROUGH LOCAL CABLE TV NETWORKS IN NAIRA - Kasmanto, Rony; Kainama, Carisz; Darmawan; Haryoko, Urip (Pusdiklat BMKG, 2023)
This change action plan is an effort to increase the percentage of the Naira community receiving weather information provided by the station. receiving weather information provided by Class III Bandaneira Meteorological Station - Central Maluku. The purpose of this change action plan is to improve the dissemination of weather information services at Bandaneira Meteorological Station through the Cable TV network, and followed by socialisation to the community to facilitate the community in accessing weather information. The change action